Contribution of Obedience According to Hannah Arendt Philosophy towards Terrorist Women in Indonesia - Munte, Alfonso; Natalia, Desi (Al Huwiyah: Journal of Woman and Children Studies, 2022)
Alienation does not only contribute to male terror actors, it turns out that women as executors have played a major role in acts of terror, especially in the last five years; before and during Covid-19. For example, women as suicide bombers. This act of terror has taken away human rights. Humans who deserve the right to life, are free from fear and a sense of security. Acts of terror seemed to be something banal. Hannah Arendt's philosophy on the banality of crime and obedience has argued that the essence of terrorism is the feeling of being left out of modern life. In addition, this article has also reviewed that people at the grassroots level in Indonesia still consider the concept of obedience by putting aside critical thoughts as a virtue and also could be a threat to humanity universally. The author had used a qualitative research method with a descriptive-interpretative approach from literature review.